2021
DOI: 10.21037/atm-21-2298
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of locally recurrent rectal cancer: a narrative review

Abstract: Objective: To summarize the recent literature on surgical treatment of locally recurrent rectal cancer (LRRC).Background: LRRC is a heterogeneous disease that requires a multidisciplinary treatment approach. The treatment and prognosis depend on the site and type of recurrence. Radical resection remains the primary method for achieving long-term survival and improving symptom control. Preoperative chemoradiotherapy can reduce tumor volume and improve the R0 resection rate. Surgeons must clearly understand pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…We observed an unexpected R1 resection in only one patient (5%). Although comparison with extant literature is extremely difficult due to the low number of patients, wide variation between LRRC patients, and selection bias, the results in this study do seem favorable compared with reported R1 resection rates up to 50% in comparable patient populations [ 6 , 7 ]. The outcome of the current study is in line with an earlier report from our group in which surgical navigation for LRRC cancer was compared with a historical control group [ 20 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We observed an unexpected R1 resection in only one patient (5%). Although comparison with extant literature is extremely difficult due to the low number of patients, wide variation between LRRC patients, and selection bias, the results in this study do seem favorable compared with reported R1 resection rates up to 50% in comparable patient populations [ 6 , 7 ]. The outcome of the current study is in line with an earlier report from our group in which surgical navigation for LRRC cancer was compared with a historical control group [ 20 ].…”
Section: Discussionmentioning
confidence: 62%
“…However, due to prior radiation and surgery, the normal surgical planes are disrupted, thus making it challenging to differentiate between fibrosis and recurrent malignancy. After surgical resection of LRRC, high tumor-positive resection margin (R1) rates are reported of 38–62% [ 6 , 7 ]. In these R1 LRRC cases, the overall five-year survival varies from 10–18% [ 8 , 9 , 10 , 11 , 12 , 13 ] compared with 48–58% among patients for whom a negative resection margin (R0) is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Definitions and classifications of recurrent CRCs are heterogeneous 16 and differ depending on the anatomic position, i.e., colonic or rectal. The definition of LR in our study combined those of The American Joint Committee on Cancer (AJCC) 17 and The Union for International Cancer Control (UICC), 18 plus the definition of the beyond TME group 7 plus our 19–21 and other LR descriptions from previous studies 3,5,22 …”
Section: Methodsmentioning
confidence: 99%
“…In the field of rectal cancer, the risk of loco-regional recurrence has been reduced by the introduction of total mesorectal excision (TME) surgery that has significantly improved loco-regional control [1][2][3][4]. Neoadjuvant (chemo) radiotherapy has further decreased the chance of locoregional recurrence in patients with locally advanced rectal cancer (LARC) [5][6][7][8].…”
Section: Purposementioning
confidence: 99%